2021
DOI: 10.3892/ijo.2021.5289
|View full text |Cite
|
Sign up to set email alerts
|

Potential of antiviral drug oseltamivir for the treatment of liver cancer

Abstract: Liver cancer is a leading cause of cancer-related mortality globally. Since hepatitis virus infections have been strongly associated with the incidence of liver cancer, studies concerning the effects of antiviral drugs on liver cancer have attracted great attention in recent years. The present study investigated the effects of two anti-hepatitis virus drugs, lamivudine and ribavirin, and one anti-influenza virus drug, oseltamivir, on liver cancer cells to assess alternative methods for treating liver cancer. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Oseltamivir, an anti-influenza virus drug, was shown to increase Beclin-1 expression and decrease p62 expression to trigger autophagy-dependent death of Huh-7 cells. 276 Moreover, regorafenib was reported to trigger autophagy-dependent cell death via blocking the interaction of Beclin-1-Bcl-2 and further promoting the dissociation of Beclin-1 from Bcl-2. 277 4-Methoxydalbergione (4MOD) had been recently reported to upregulate Beclin-1 and LC3-II/LC3-I, inducing autophagy-dependent cell death and thus inhibiting the growth of J82 and UMUC cells, which accompanied with the suppression of Akt/ERK pathway.…”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…Oseltamivir, an anti-influenza virus drug, was shown to increase Beclin-1 expression and decrease p62 expression to trigger autophagy-dependent death of Huh-7 cells. 276 Moreover, regorafenib was reported to trigger autophagy-dependent cell death via blocking the interaction of Beclin-1-Bcl-2 and further promoting the dissociation of Beclin-1 from Bcl-2. 277 4-Methoxydalbergione (4MOD) had been recently reported to upregulate Beclin-1 and LC3-II/LC3-I, inducing autophagy-dependent cell death and thus inhibiting the growth of J82 and UMUC cells, which accompanied with the suppression of Akt/ERK pathway.…”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…182,183 In addition, the antiviral drug ribavirin catalyses ACHY conversion to adenosine and Hcy and then blocks the activity of ACHY. [141][142][143][144][145][146] 3′keto aristeromycin and 2-fluoroadenosine displayed the in vivo suppression activity of ACHY. 147 Hao et al screened thirteen compounds inhibiting ACHY by ChemMapper and SciFinder Scholar, which greatly increased the candidates for clinical research, and found that Compound 13 exerted considerable inhibitory effects on breast cancer and prostate cancer [152][153][154] (Figure 3 and Table 4).…”
Section: Achy Inhibitorsmentioning
confidence: 98%
“…Cu 2+ inhibited the enzymatic activity of ACHY by inducing the release of NAD + cofactors 182,183 . In addition, the antiviral drug ribavirin catalyses ACHY conversion to adenosine and Hcy and then blocks the activity of ACHY 141–146 . 3′‐keto aristeromycin and 2‐fluoroadenosine displayed the in vivo suppression activity of ACHY 147 .…”
Section: Target 1c Metabolism Enzymes For Cancer Immunotherapymentioning
confidence: 99%
“…Recently, Huang et al in 2021 reported the differential effect of oseltamivir in inducing liver cancer cell death both in vitro and in vivo. Treatment with oseltamivir decreased migration and invasion of liver cancer cells and increased autophagy in Huh-7 cells . Urtishak et al also reported that the antiviral drug ribavirin decreased the elevated level of EIF4E protein in most cases of infant acute lymphoblastic leukemia (ALL) .…”
Section: Antiviral Strategiesmentioning
confidence: 99%